Therapeutic intervention scoring system-28 (TISS-28): diretrizes para aplicação Therapeutic intervention scoring system-28 (tiss-28): directrices para su aplicación Therapeutic intervention scoring system-28 (tiss-28): directions for application - Katia Grillo Padilha; Regina Marcia Cardoso de Sousa; Ana Maria Kazue Miyadahira; Diná de Almeida Lopes Monteiro da Cruz; Maria de Fátima Fernandes Vattimo; Miako Kimura; Sonia Aurora Alves Grossi; Maria Claudia Moreira da Silva; Valéria Ferraz Cruz; Adriana Janzanti Ducci (SciELO, 2005)
O Therapeutic Intervention Scoring System-28 (TISS-28) é um instrumento que permite dimensionar carga de trabalho de enfermagem em Unidade de Terapia Intensiva e estimar gravidade da doença. Apresenta-se nesta publicação as definições operacionais para sua aplicação, proposta por um grupo de especialistas na área, com vistas a uniformizar o significado de cada um dos itens e evitar vieses de interpretação. El Therapeutic Intervention Scoring System-28 (TISS-28) es un instrumento que permite dimensionar carga de trabajo de enfermería en una Unidad de Terapia Intensiva y estimar la gravedad de la enfermedad. Se presenta en esta publicación las definiciones operacionales para su aplicación, propuesta por un grupo de especialistas en el área, con vistas a uniformizar el significado de cada uno de los items y evitar sesgos de interpretación. Therapeutic Intervention Scoring System-28 (TISS-28) is a tool that enables the measurement of the nursing work load in Intensive Care Units and the estimate of how grave the disease is. In this study are presented the operational definitions for its application, proposed by a group of specialists in the area, with the aim of rendering uniform the meaning of each of the items and preventing interpretation biases.